2021
DOI: 10.3390/ijerph182312419
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Diagnosis of Dyslipidemia: ESCARVAL-GENERO

Abstract: Evidence shows that objectives for detecting and controlling dyslipidemia are not being effectively met, and outcomes differ between men and women. This study aimed to assess gender-related differences in diagnostic inertia around dyslipidemia. This ambispective, epidemiological, cohort registry study included adults who presented to public primary health care centers in a Spanish region from 2008 to 2012, with dyslipidemia and without cardiovascular disease. Diagnostic inertia was defined as the registry of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
2
11
1
2
Order By: Relevance
“…Our findings are consistent with the findings reported by Soriano-Maldonado et al who provided researchbased evidence that dyslipidemia is heterogeneous based on gender and it differs significantly between males and females in terms of prevalence and risks [23].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with the findings reported by Soriano-Maldonado et al who provided researchbased evidence that dyslipidemia is heterogeneous based on gender and it differs significantly between males and females in terms of prevalence and risks [23].…”
Section: Discussionsupporting
confidence: 93%
“…Another cross-sectional study conducted on 275 volunteered diabetic patients showed significant increase in all examined lipid parameters (TC, TG, LDL-C) and calculated indexes (lipid accumulation product, visceral adiposity index) across HBA1c three groups, with exception of HDL-C that decreased along with increment in HBA1c, TC (OR = 1.46, 95% CI (1.18-1.81), P = 0.001), TG (OR = 1.44, 95% CI (1.18-1.76), P < 0.001), and LDL-C (OR = 1.42, 95% CI (1.11-1.83), P = 0.006), increased by 1 mmol/L each, probabilities of higher HBA1c increased by 46%, 44% and 42%, respectively [ 23 ]. High TC and TG were the independent predictors of higher HBA1c.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study is consistent with prior studies suggesting associations between covariates and dyslipidemia, such as gender [ 79 ], urban–rural difference [ 77 ], marital status [ 80 ], age [ 29 ], years of education [ 81 ], smoking status [ 82 ], and alcohol use [ 83 , 84 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, many clinical variables not recorded in the EHR were detected. In a previous study of the same cohort but a dyslipidemic population, 18% of adults met the diagnostic criteria for dyslipidemia and had no recorded diagnosis or treatment prescribed (DI), with DI greater in women, young age, normal weight, no smoking habit, and those with alterations in SBP, HDL cholesterol, total cholesterol, LDL cholesterol, or triglycerides, or missing values in their EHR ( 28 ). A similar pattern exists between both sexes, and in DI in both hypertension and dyslipidemia, there is a lack of assessment of subclinical disease (comorbidities).…”
Section: Discussionmentioning
confidence: 99%
“…had no recorded diagnosis or treatment prescribed (DI), with DI greater in women, young age, normal weight, no smoking habit, and those with alterations in SBP, HDL cholesterol, total cholesterol, LDL cholesterol, or triglycerides, or missing values in their EHR (28). A similar pattern exists between both sexes, and in DI in both hypertension and dyslipidemia, there is a lack of assessment of subclinical disease (comorbidities).…”
Section: Discussionmentioning
confidence: 99%